Collected works of George Grant. - Grant, George Parkin, 1918-1988 (University of Toronto Press, 2005)
In this, the third volume of the Collected Works of George Grant, editors Arthur Davis and Henry Roper have gathered together Grant's work from the 1960s, when he was a professor at Hamilton, Ontario's McMaster University.